The Position of the Police Code of Ethics Commission in The Judicial Power System in Indonesia - Yusuf Warsyim; Harmoko Harmoko (Jurnal Hukum dan Peradilan, 2024)
The Police Code of Ethics Commission has the authority to advocate violations of the Police Code of Ethics. The presence of the National Police Code of Ethics Commission gave rise to serious conceptual debates. As a rule of law with an independent judicial power as its main element, theoretically, judicial power can only be owned by state institutions that are constitutionally recognized in the 1945 Constitution, namely the Supreme Court and the Constitutional Court, but in its development, the function of Judicial power is not only exercised by the courts. This study aims to determine the position of the Polri Code of Ethics Commission and the relationship between the Polri Code of Ethics Commission and the judicial power system in Indonesia. The method used is normative research, with a conceptual approach and laws and regulations. The results of the study found that the position of the Polri Code of Ethics Commission in the judicial power system has been accommodated in the Judicial Power Law, and the relationship that is built between the Code of Ethics Commission and the Supreme Court is a functional relationship.